Do neurocognitive functions in cannabis induced psychosis groups differ from schizophrenia with cannabis use? A controlled cross-sectional study. (1st September 2021) - Shah, Raghav; Ghosh, Abhishek; Avasthi, Ajit; Nehra, Ritu; Ahuja, Chirag K.; Khandelwal, Niranjan
Abstract: Objective: Cannabis-induced psychosis (CIP) has received little research attention. We compared neurocognitive functions in CIP, Schizophrenia with cannabis use (SZC) and healthy control group (CG). Methods: Twenty age, education, and handedness-matched participants were recruited in each of the three groups. CIP and SZC were diagnosed with Psychiatric research interviews for substance use and mental disorders. Level of cannabis exposure, global intelligence, executive function, attention, vigilance, working, and verbal memory, and motor speed were compared by analysis of variance with post-hoc Scheffe's test. We did a post-hoc power calculation. Results: Age at initiation, frequency, duration, and preparation of cannabis use did not differ significantly between CIP and SZC. CIP performed significantly better (than SZC) in tests of general cognitive ability or intelligence and attention, perceptual tracking and sequencing. SZC showed significant dysfunctions (than CG) in all parameters of the tests for executive dysfunction, sustained attention, short-term verbal memory and psychomotor functioning. CIP and CG did not differ in any cognitive domains except for non-perseverative errors in the test for executive functioning. Conclusions: CIP and SZC had different degrees of impairment compared to controls, but on direct comparisons CIP had better general intelligence and attention. KEY POINTS: Cannabis-induced psychosis (CIP) may have different neurocognitive impairment than Schizophrenia with cannabis use (SZC) CIP performed better in tests for general intelligence and visual attention than SZC SZC had significant impairment in executive function, attention, verbal memory, and psychomotor speed than controls Compared to controls, CIP performed significantly worse in some domains of executive function CIP and SZC had different degrees of cognitive impairments as compared to the controls